(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
In this article we problematize the common keys between critical extension and feminist epistemology. For this purpose, we base on our experience from our experience in university teaching and how feminisms have also permeated our work at the university, in extension, teaching and research. We conceptualize Latin American and Caribbean Critical Extension, then we make a background review of productions from different latitudes that have contributed to thinking about the relationship between extension and feminism. In this same sense, we place some of the common keys that we have found in this journey, such as: situated knowledge, criticism of conventional science and its ways of producing knowledge, as well as claiming implicated and committed knowledge.